Volunteering in Sport - Bácsné Bába, Éva; Bács, Zoltán; Pető, Károly; Müller, Anetta; Pfau, Christa; Dajnoki, Krisztina; Molnár, Anikó (International Journal of Engineering and Management Sciences, 2018)
The subject of our research was the examination of the sports ambition and its motivational background. Our aim was to examine the volunteer experience of young adults in volunteering. Our goal was also to analyze the areas in which sports are chosen most voluntarily and what motivates them in sport. The basis for our questionnaire research was the concept of volunteering "4 W" (who, what, where, why). The questionnaire was designed to answer these questions in relation to sports ambition. The data of the questionnaire completed by 371 young adults (mean age = 23.93, sd = 9.93) were analyzed using SPSS statistical software, where we calculated basic statistics (mean, standard deviation, median, mode) and Chi2 test. More than 75% of the respondents have already worked as volunteers. One of the most popular areas of volunteering was sport. The most frequented volunteering area was among schoolchildren and students as well as university sports among young people, after which the area of competition and recreational sports proved to be the most popular. The main motivation of young volunteer workers was the following, : „I had a good mood”, „I loved sport”, „teamwork”, „work experience”, „learning and skill development” and „career perspective”. Organizations, marketing and communication areas in the field of sporting events and sportsclubs volunteering were the most popular in the area where the respondents had experience. A significant difference was found in the field of organizing and marketing volunteering in sports events, 61% of Hungarians worked, while respondents from other countries were only 34.2% (p <0.05). In the field of communication, higher values of respondents from other countries (45.7%), compared with Hungarians (33.7%) (p <0.05).